2001
DOI: 10.2500/108854101778250571
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in Tears and Sera in Patients with Atopic Dermatitis

Abstract: The aim of the study was to investigate the role of circulating (i.e., present in the serum) and locally produced (i.e., in the lamina propria of mucous membranes) immunoglobulins including IgE. The IgG, IgA, IgM immunoglobulins, and IgE (total and specific) were measured in patients' sera with atopic dermatitis (AD) (n = 93). As control subjects 83 healthy volunteers, matched for sex and age, were included. The IgG and IgM levels were within the normal range. Mean value of the total IgA (2.55 +/- 0.26 g/L, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…reported the normal level of other Igs in HIS. It has been found that the IgG and IgM levels were within the normal range but the total IgA and IgE levels were significantly elevated in sera of AD patients 21 . In AIDS patients the levels of all classes of immunoglobulin were elevated 22 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…reported the normal level of other Igs in HIS. It has been found that the IgG and IgM levels were within the normal range but the total IgA and IgE levels were significantly elevated in sera of AD patients 21 . In AIDS patients the levels of all classes of immunoglobulin were elevated 22 .…”
Section: Discussionmentioning
confidence: 96%
“…It has been found that the IgG and IgM levels were within the normal range but the total IgA and IgE levels were significantly elevated in sera of AD patients. 21 In AIDS patients the levels of all classes of immunoglobulin were elevated. 22 The exact mechanism in the regulation of other immunoglobulins by Th1 and Th2 was largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CD20 is a B cell-specific marker whose expression is initiated during late pre-B cell development and lost during plasma cell differentiation (35,36). The levels of IgA and IgE in blood were generally elevated in patients with atopic dermatitis (37). Studies have shown that high proportions (ranging 60-92%) of human blood plasma cells express IgA (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of total tear IgE is useful for the diagnosis of allergic conjunctivitis [1,2,3]. Several research groups have reported a new method of measuring total tear IgE by immunochromatography [4,5,6,7]. Recently, a new commercial kit was released (Allerwatch®, Hitachi Chemical Co., Ltd., Tokyo, Japan, and Wakamoto Pharmaceutical Co., Ltd., Tokyo, Japan), which is a rapid immunoassay for measuring the total tear IgE level.…”
Section: Introductionmentioning
confidence: 99%